Anthropocene - Burtynsky, Edward 1955- (Goose Lane Ed., 2018)
Published to coincide with the new exhibition featuring the work of photographer Edward Burtynsky, and the release of a film on the same topic by Jennifer Baichwal and Nicholas de Pencier, Anthropocène chronicles the massive and irreversible impact of humans on the Earth.0In photographs that are both stunning and disconcerting, along with essays by artists, curators and scientists, this important catalogue brings contemporary art into conversation with environmental science and anthropology, on a topic that urgently affects all of us. 00Exhibition: Art Gallery of Ontario, Toronto, Canada (18.09.2018 - Spring 2019) / National Gallery of Canada, Ottawa, Canada (18.09.2018 - Spring 2019) / Fondazione MAST, Bologna, Italy (Spring 2019)
Keywords: Burtynsky, Edward -- 1955-; Umweltverschmutzung; Dokumentation; Anthropozän; Ausstellungskatalog -- Art Gallery of Ontario -- 18.09.2018-Spring 2019 -- Toronto, Canada; Ausstellungskatalog -- National Gallery of Canada -- 28.09.2018-06.01.2019 -- Ottawa, Ontario, Canada; Ausstellungskatalog -- Fondazione MAST -- 2019 -- Bologna, Italy